A Bibliometric Analysis of Global Research on Dementia and its Cognitive Function - Pahantasingh, Suchismita; Das, Sasmita; Sahoo, Surjeet; Dash, Manoranjan; Tripathy, Pravati; Pradhan, Jhunilata; Samantaray, Krishna Kumari; Pradhan, Rubi (AL-Kindy College Medical Journal, 2025)
Introduction: Dementia is a neurocognitive disease manifested by progressive and global declination in cognition. However, there is a lack of visualization analysis on research in the field of dementia and cognitive function. To evaluate the impact and compare the scholarly work output and productivity among organizations, bibliometrics was used.Material and methods Literature related to dementia and cognitive function were searched from Scopus database. In the area of dementia bibliometrics was used to analyze the leading authors, the journals with higher citation, higher collaboration between the countries, and keywords. Scopus analysis and Biblioshiny R-package were used in the analysis of country collaboration and global cited documents.Results: Total 1753 articles were identified from Scopus database and among these 425 articles were included in the study on basis of inclusion criteria. United states, China and Japan has the highest productivity and China, USA, Australia, Canada and Indonesia and has strong collaboration. The research hotspots in this field focused on Dementia and its impact on cognitive function. According to Lotka’s Law the studies in the field of dementia is limited and need to be conducted further.Conclusion: Dementia is a major public health issues in India and this study has thrown light on all articles which has manifested the current trends and important areas of research on dementia.  After an intensive analysis the study concluded that there is still a gap in international collaboration among leading countries. In India dementia can be a research gray area and focus of future attention.